Jonquilla - being your own worst enemy - Liaw, Cheryn Yu Ting (Nanyang Technological University, 2022)
Jonquilla explores the idea of self-perception and self-compassion, and how misjudgement of one’s personal abilities affects their mental state. Self-perception often refers to a person’s attitude and treatment towards themselves, and self-compassion has been a struggle that many people face, especially as they figure out their identity and placement in this world.